2013
DOI: 10.9738/cc156.1
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Role of Totally Extraperitoneal Repairs for Groin Pain in Athletes

Abstract: A literature review was made on the role of totally extraperitoneal (TEP) hernia repairs for groin pain in athletes. Electronic databases were searched for literature published from January 1993 to November 2011. There were 10 articles incorporating 196 patients included in this review. Thirty percent of patients were reported to have direct inguinal hernias, 22% had indirect inguinal hernias, and 41% had dilated internal rings. Of note, 30% of cases had no macroscopic abnormality. Four studies reported on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…They reported that a new-onset hernia was identified in 65% and true inguinal hernia in 35% of the patients in a series of 55 sportsmen. Recent studies recommend that surgical treatment should now be selected as the first treatment method by skipping conservative treatment in order to treat inguinal pain in sportsmen (39). It could be stated that our own practice is also in parallel with the literature in that sense.…”
Section: Surgical Treatment Options Are Laparoscopic (Tep or Tapp) Anmentioning
confidence: 96%
See 3 more Smart Citations
“…They reported that a new-onset hernia was identified in 65% and true inguinal hernia in 35% of the patients in a series of 55 sportsmen. Recent studies recommend that surgical treatment should now be selected as the first treatment method by skipping conservative treatment in order to treat inguinal pain in sportsmen (39). It could be stated that our own practice is also in parallel with the literature in that sense.…”
Section: Surgical Treatment Options Are Laparoscopic (Tep or Tapp) Anmentioning
confidence: 96%
“…Many surgeons have acknowledged that laparoscopic therapy, which has an increasing popularity among surgical treatments, ensures an effective and quicker return to full sports activity (87-92% of patients in 2-8 weeks) (20,23,35,(39)(40)(41)(42). Genitsaris (42) stated in his study that 97% of his patients returned to full sports activity in 2-3 weeks.…”
Section: Surgical Treatment Options Are Laparoscopic (Tep or Tapp) Anmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent randomised trial including 60 athletes with ID/AP, the efficacy of TEP compared with non-operative treatment was further confirmed 18. A recent review summarises that TEP repair is a good alternative in athletes with intractable groin pain who do not respond to non-operative treatment strategies 30. This review examined 10 publications that incorporated 196 patients from a literature search of electronic databases from January 1993 to November 2011.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%